An investigation of behaviour and attitudes relevant to the user safety of pedestrian/cyclist shared paths. (July 2016) - Hatfield, Julie; Prabhakharan, Prasannah
Highlights: On shared paths in Australia (left-hand traffic). Cyclists were more likely than pedestrians to keep left. Centreline marking was associated with keeping left (pedestrians and cyclists). Centreline marking was associated with lower cycling speeds. Mobile phone and mp3 use was common. Overtaking on the right, not keeping left, and device-use, may reduce safety. Abstract: Bicycle/pedestrian shared paths are an increasingly popular solution to providing cycling infrastructure, despite evidence suggesting safety issues. Improved design and management of shared paths should be informed by understanding of bicyclist and pedestrian behaviour on shared paths, and of relevant safety initiatives (e.g. centreline marking). However, relevant research is lacking. Bicyclist/pedestrian passing events ( n  = 407) were observed on three relatively busy shared paths in Sydney, Australia – one of them without centreline marking. User characteristics, relevant behaviours and incidents (aggression, near-misses, crashes) were recorded. A tendency toward left-hand travel, as on Australian roads, was stronger for cyclists than for pedestrians, and where centreline was present. Cyclists were often estimated to travel above 10 km/h, a speed limit that has been suggested based on pedestrian safety considerations, but that would be unacceptable for long stretches of commuter cycling. Centreline was associated with lower estimated speeds. Cyclists typically adhered to their responsibility of giving way to pedestrians, but often passed on the left, passed too close, passed without slowing, or passed without warning (e.g. with a bell). Use of mobile telephones and mp3 players is common, particularly amongst pedestrians. Five near collisions were observed, and 53 survey participants reported 2 collisions and 13 near misses. Contributing factors appear to include path users using potentially distracting devices, or straying from the rules of thumb to keep to the left, and to overtake on the right. A survey of cyclists and pedestrians suggested that there are issues with perceptions of space ownership. These results represent an important contribution to the evidence-base for initiatives to improve the safety of shared paths.